RISAN: Robust Instance Specific Deep Abstention Network - Shah, Kulin; Kalra, Bhavya; Manwani, Naresh (The 37th Conference on Uncertainty in Artificial Intelligence (UAI 2021), 2021)
In this paper, we propose deep architectures for learning instance specific abstain (reject option) bi-nary classifiers. The proposed approach uses double sigmoid loss function as described by Kulin Shah and Naresh Manwani in ("Online Active Learning of Reject Option Classifiers", AAAI,2020), as a performance measure. We show that the double sigmoid loss is classification calibrated. We also show that the excess risk of 0-d-1 loss is up-per bounded by the excess risk of double sigmoid loss. We derive the generalization error bounds for the proposed architecture for reject option classifiers. To show the effectiveness of the proposed approach, we experiment with several real world datasets. We observe that the proposed approach not only performs comparable to the state-of-the-art approaches, it is also robust against label noise. We also provide visualizations to observe the important features learned by the network corresponding to the abstaining decision.